ANALYSIS OF MEASURING STOCK OPNAME OF CEMENT SUPPORTING RAW MATERIALS BY TOTAL STATION - Rahmania, Tsabita Bayu; Kristian, Naomy Elliana (Marine & Earth Science and Technology Research Center, DRPM, ITS, 2023)
PT Semen Indonesia (Persero) Tbk is a BUMN (State-Owned Enterprise) company that operates in the cement industry in Indonesia and even abroad. PT Semen Indonesia (Persero) Tbk is located in Sumberarum Village, Kerek District, Tuban Regency, East Java Province. PT. Semen Indonesia (Persero) Tbk implements an open pit mining system using the Quarry method. This company is always close to mining activities where they can run if they meet the requirements of the Work Plan and Budget (RKAB) requirements per the Decree of the Minister of Energy and Mineral Resources No. 1806 K/30/MEM/2018. Mining activity planning is the most crucial aspect in designing mine designs, as a reference for achieving production targets and analyzing stock reserves of production raw materials. Stock taking is a temporary storage place after undergoing the transportation process from the mining front so that it can be ensured that the quality of the limestone can be maintained as originally. (Aliyusra Jolo, 2017). The method used in this research involves field surveys, taking detailed points according to the shape of the appearance, and processing the data using AutoCAD Civil 3D software which has a Triangular Irregular Network (TIN) working concept. The results of the research show that in stock-taking, after calculating the area and volume, we obtained an area of 4634,266 m² for stock opname 1, an area of 2916,728 m² for stock-taking 2, 1669,189 m² for stock-taking 3, and the total area of stock opname was 6298,750 m². And for the volume itself, the resulting volume was 24,204,084 m³ for stock opname 1, an area of 14,263,732 m³ for stock opname 2, 4321,165 m³ for stock opname 3, and the overall stock opname area was 42,788,981m³. As a result, this limestone stock will be used as a supporting material for cement production.